Dynamics of Omnibus Law Formation: Between Legislative Efficiency and Potential Legal Chaos - Al-Fatih, Sholahuddin; Ranendra, Bagas; Tajrim, Muhammad Ikhsan; AllahRakha, Naeem (Jurnal Hukum Replik, 2025)
The Omnibus Law method represents a novel approach in the Indonesian legislative framework, initially embodied in Law Number 11 of 2020 on Job Creation. This method unify diverse sectoral regulations into a singular legal framework to enhance economic growth and streamline investment processes. However, it faces substantial criticism regarding its legitimacy, notably for inadequate public participation and potential legal ambiguities that may arise from overlapping norms. The integration of the Omnibus Law, influenced by common law traditions, presents compatibility challenges within Indonesia's civil law system, which emphasizes a hierarchical legal structure. The absence of explicit procedures for enacting Omnibus Laws in existing legislation has resulted in fears of legal uncertainty and procedural violations, particularly manifest in the rapid and non-inclusive passage of the Job Creation Law. Critics caution that this approach undermines democratic processes by lacking transparency and public input, as evidenced by widespread protests reflecting public discontent. Additionally, the consolidation of various regulations raises concerns regarding interpretative conflicts and implementation difficulties, posing risks to compliance and governance efficiency. The Constitutional Court has deemed the law "conditionally unconstitutional," underlining its procedural shortcomings. Despite these issues, the Omnibus Law holds potential for simplifying complex regulations and fostering investment, contingent upon enhanced transparency, accountability, and public engagement. Consequently, while the Omnibus Law method could significantly reform Indonesia's legislative landscape by providing adaptive solutions for contemporary challenges, its successful implementation necessitates careful formulation and a commitment to preserving justice and equity within the legal process.